An android-based start-up app for self-agriculture and food - Agung, Pangestu; Rosyid Ridlo, Al Hakim; Hexa Apriliana, Hidayah; Ariep, Jaenul; Yanuar Zulardiansyah, Arief; R., Ekawati (IOP Publishing, 2023)
Several sectors, including technology, influence the need for food to date. Global heating conditions also impact the existing food system since poor agricultural conditions reduce farm product output and increase famine risk. As cybernated start-ups develop, it enables multiple parties to develop start-ups in farming and food sectors. This study aims to develop a self-agriculture and food start-up app based on Android OS. This application allows each user to prepare and commercialise food items autonomously. The system is intended to encourage individuals to perform tasks such as cultivating and selling harvests, purchasing dietary commodities, and monitoring current microclimate circumstances.